Quasi static and dynamic inelastic buckling and failure of folded-plate structures by a full-energy finite strip method. (March 2018) - Milašinović, D.D.; Majstorović, D.; Vukomanović, R.
Highlights: The RDA reduces material nonlinear problems to linear dynamic problems. A study of uniformly compressed folded-plate structures. Finite strip method. Modulus iterative method for the solution of nonlinear equations. The quasi-static and dynamic inelastic buckling and failure. Abstract: A study on how a mathematical material modeling approach named rheological-dynamical analogy (RDA) can be used to predict the quasi static and dynamic inelastic buckling and failure of structures is presented in this paper. An analysis of the uniformly compressed folded-plate structures, made of isotropic materials, is carried out. Two sources of non-linearity, one involving geometrical non-linearity due to large deflection, and the other involving material non-linearity due to inelastic behavior, are analyzed by implementing a full-energy finite strip method (FSM). The material non-linearity is analyzed using the RDA. A very basic continuum damage model with one damage parameter is implemented in conjunction with a mathematical material modeling approach in order to address stiffness reduction due to inelastic behavior. According to the analogy, a very complicated material non-linear problem in the inelastic range of strains is solved as a simple linear dynamic one. The orthotropic constitutive relations are derived and modulus iterative method for the solution of nonlinear equations is presented.